Development of the Geo-Food Board Game to Improve Geometry Skills Based on Van Hiele’s Levels of Thinking in Fourth Grade Elementary Students - Laurencia Lucia Rosok Klau Muti; Dani Kusuma (SAINTIS Publishing, 2025)
The lack of interactive learning media in mathematics education, particularly in geometry, often makes it difficult for students to understand the material and leads to boredom during learning. Therefore, there is a need for game-based media that engages students and encourages active participation in classroom learning. This study aims to examine the development process, validity, effectiveness, and practicality of the